HART PROTOCOL ANALYSER BASED IN LABVIEW - Dias Pereira, J. M.; Postolache, Octavian; Silva Girao, P. (International Journal of Computing, 2014)
Analysis of Highway Addressable Remote Transducer (HART) protocol is important in reliability evaluation of HART based systems. The present work proposes a virtual instrument based solution for HART signal analysis that includes a digital oscilloscope with GPIB interface, a HART modem, a PC with a GPIB interface board and a RS232 port, and a software component developed in LabVIEW. The HART analyser permits the visualisation of signals that correspond to the HART protocol, gives access to data coming from field instruments and has the ability to analyse and modify field instrument performance.